Dampak kecerdasan buatan terhadap ketimpangan pendapatan di sektor manufaktur - Jailani, Mohammad Shohibul Fajar (Maliki Interdisciplinary Journal, 2024)
This study examines the impact of artificial intelligence (AI) on income inequality in the manufacturing sector. While AI offers significant improvements in efficiency and productivity, its implementation tends to widen the gap between large companies that can invest in advanced technology and small and medium-sized enterprises (SMEs) that struggle to adapt. Additionally, automation driven by AI poses a risk of displacing routine jobs, particularly for low-skilled workers, creating a bifurcation in the labor market. Therefore, this research emphasizes the importance of inclusive policy interventions, such as investment in education, support for SMEs, and reskilling programs, to ensure that all segments of society can benefit from technological advancements. With the right approach, the manufacturing sector can develop sustainably and equitably.